Health economics in the field of osteoarthritis - Hiligsmann, Mickaël (2022)
Funding Information: M.H. (Mickael Hiligsmann) has received research grant, lecture fees, and/or consulting fees from Amgen, Pfizer, Novartis, Servier, and SMB. C.C. has received honoraria and consulting fees from AMGEN, GSK, Alliance for Better Bone Health, MSD, Eli Lilly, Pfizer, Novartis, Servier, Medtronic, and Roche. M.-L.B. was consultant and grant recipient from Amgen, Eli Lilly, MSD, Novartis, NPS, Roche, and Servier. O.B. has received grant research from IBSA, Merck Sharp & Dohme, Nutraveris, Novartis, Pfizer, Rottapharm, Servier, and Theramex; consulting or lecture fees from IBSA, Rottapharm, Servier, and SMB; and reimbursement for attending meetings from IBSA, Merck Sharp & Dohme, Novartis, Pfizer, Rottapharm, Servier, and Theramex. M.H. (Marc Hochberg) was a member of the Scientific Advisory Board of TREAT-OA Consortium; has served as a consultant to Abbott Laboratories, Allergan, Bioiberica S.A., Covidien, Iroko Pharmaceuticals, Merck & Co., and Pfizer Inc; and received speaker fees from Bioiberica S.A. and IBSA. D.H. receives royalties from DJO. T.K. has received fees for speaking from Abbott, AstraZeneka, Hospira, MSD/Schering-Plough, Nicox, Pfizer/Wyeth, Roche, and UCB; funds for research from Diakonhjemmet Hospital from Abbott, BMS, MSD/Schering-Plough, Pfizer/Wyeth, Roche, and UCB; and fees for consulting from Abbott, BMS, MSD/Schering-Plough, Nicox, Pfizer/Wyeth, Roche, and UCB. S.S. has served as an advisor for Lilly, Novartis, and Pfizer/Wyeth; has served as a consultant for Genentech, Lilly, Novartis, and Pfizer/Wyeth; and has received research support from Lilly and Pfizer/Wyeth. R.R. has received consulting and lecture fees for Merck Sharp and Dohme, Eli Lilly, Amgen, Novartis, Servier, Nycomed, Nestlé, and Danone. L.R. is an employee of Rottapharm. Y.T. is an employee of Servier. P.T. has received from UCB, Chelsea, and BMS. J.-Y.R. has received consulting fees, paid advisory boards, lecture fees, and/or grant support from Servier, Novartis, Negma, Lilly, Wyeth, Amgen, GlaxoSmithKline, Roche, Merckle, Nycomed, NPS, Theramex, UCB, Merck Sharp and Dohme, Rottapharm, IBSA, Genevrier, Teijin, Teva, Ebewee Pharma, Zodiac, Analis, Novo-Nordisk, and Bristol Myers Squibb.